Evaluation of non‐coding variation in GLUT1 deficiency. (6th June 2016) - Liu, Yu‐Chi; Lee, Jia Wei Audrey; Bellows, Susannah T; Damiano, John A; Mullen, Saul A; Berkovic, Samuel F; Bahlo, Melanie; Scheffer, Ingrid E; Hildebrand, Michael S; ,
Abstract : Aim: Loss‐of‐function mutations in SLC2A1, encoding glucose transporter‐1 (GLUT‐1), lead to dysfunction of glucose transport across the blood–brain barrier. Ten percent of cases with hypoglycorrhachia (fasting cerebrospinal fluid [CSF] glucose <2.2mmol/L) do not have mutations. We hypothesized that GLUT1 deficiency could be due to non‐coding SLC2A1 variants. Method: We performed whole exome sequencing of one proband with a GLUT1 phenotype and hypoglycorrhachia negative for SLC2A1 sequencing and copy number variants. We studied a further 55 patients with different epilepsies and low CSF glucose who did not have exonic mutations or copy number variants. We sequenced non‐coding promoter and intronic regions. We performed mRNA studies for the recurrent intronic variant. Results: The proband had a de novo splice site mutation five base pairs from the intron–exon boundary. Three of 55 patients had deep intronic SLC2A1 variants, including a recurrent variant in two. The recurrent variant produced less SLC2A1 mRNA transcript. Interpretation: Fasting CSF glucose levels show an age‐dependent correlation, which makes the definition of hypoglycorrhachia challenging. Low CSF glucose levels may be associated with pathogenic SLC2A1 mutations including deep intronic SLC2A1 variants. Extending genetic screening to non‐coding regions will enable diagnosis of more patients with GLUT1 deficiency, allowing implementation of the ketogenic diet to improve outcomes. What this paper adds: Deep intronic SLC2A1 mutations may cause GLUT1 deficiency. Awareness of age‐related cerebrospinal fluid glucose levels critical in GLUT1 deficiency evaluation. Sequencing of SLC2A1 is worthwhile when GLUT1 deficiency is suspected. This article is commented on by van Karnebeek on pages1210–1211 of this issue.